Technology -Enhanced Personalized Footwear for Mobility and Rehabilitation in Limb Length Discrepancy - Bijin Samuel Roy; Grace Francis; Rohith N; Kartik Siva; Abdul Rahuman M (International Journal of Scientific Research in Science and Technology, 2024)
This research paper explores the development, utilization, and impact of technology-enhanced footwear designed specifically for individuals with Limb Length Discrepancy (LLD). Drawing upon a multidisciplinary approach that combines biomechanics, orthopedics, and engineering, the study investigates the diverse range of innovative solutions that have been devised to address the challenges associated with LLD. Key components of this inquiry include the integration of adjustable heel lifts, custom orthotic insoles, and advanced materials such as 3D-printed soles. These technologies not only aid in reducing pain and discomfort associated with LLD but also promote improved balance, gait, and overall functionality. Moreover, technology-enhanced footwear offers a versatile platform for rehabilitation exercises, enabling individuals with LLD to regain strength and coordination. Furthermore, this paper examines the user experience and satisfaction levels associated with technology-enhanced footwear, shedding light on the practical benefits and potential limitations of these solutions. Through a comprehensive review of existing literature and case studies, we highlight the effectiveness of these innovations in improving the daily lives of individuals affected by LLD.
Keywords: Limb Length Discrepancy; Technology-Enhanced Footwear; Rehabilitation Solutions; Mobility Enhancement; Orthopedic Footwear; Adjustable Heel Lifts